2020
DOI: 10.3389/fphar.2020.593392
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Modified Systemic Inflammation Score in Patients With Extranodal Natural Killer/T-Cell Lymphoma

Abstract: NLR and Alb level to establish a modified systemic inflammation score (mSIS). These 184 patients were divided into 3 groups: group 1 (mSIS score of 0), group 2 (mSIS score of 1), and group 3 (mSIS score of 2). The mean OS of these three groups were 42 months (95% CI: 31.4-53.12), 77 months (95% CI: 68.5-87.5), and 89 months (95% CI: 71.4-82.7), respectively (P < 0.001). The Harrell's concordance index (C-index) of mSIS is 0.725. The mSIS could be used to discriminate patients categorized in the low-risk group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The mSIS was modified from the SIS to include a fixed value of 3.4 for the LMR as opposed to the median. Recently, more scholars have adopted the mSIS ( 7 , 8 , 23 , 26 ). We found that the mSIS was significantly correlated with postoperative unplanned admission to the ICU in patients with NSCLC, especially in patients with a mSIS of 2 (ALB < 4.0 g/d and LMR < 3.4).…”
Section: Discussionmentioning
confidence: 99%
“…The mSIS was modified from the SIS to include a fixed value of 3.4 for the LMR as opposed to the median. Recently, more scholars have adopted the mSIS ( 7 , 8 , 23 , 26 ). We found that the mSIS was significantly correlated with postoperative unplanned admission to the ICU in patients with NSCLC, especially in patients with a mSIS of 2 (ALB < 4.0 g/d and LMR < 3.4).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported that mSIS, which is determined according to the LMR and serum albumin concentration before surgery, is the new inflammation-related prognosis scoring system. Researchers have identified that mSIS is of prognostic value for GC, lymphoma, and ESCC ( 12 14 ). It takes into account the effects of systemic inflammation together with the nutritional status on cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Galizia et al have first reported that a new scoring system according to the LMR and albumin concentration in serum, which was called the modified systemic inflammation score (mSIS) and it might comprehensively reflect nutritional status and systemic inflammation in patients with cancer (11). The mSIS was strongly related to the survival for patients with GC, esophageal squamous cell carcinoma (ESCC), and lymphoma (12)(13)(14). Besides, it is suggested that, compared with other prognostic factors, including the modified Glasgow Prognostic Score and the original systemic inflammation score, the mSIS is more accurate in predicting survival (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The important issue here is which factor should be added to the traditional inflammatory parameters for mSIS. While Chang et al used Alb for modification, Huang He et al used CRP [ 20 ]. Both of these two parameters have been recently been added to the SIS scoring system.…”
Section: Dıscussıonmentioning
confidence: 99%